Pemberdayaan Masayarakat Desa Watu melalui Kewirausahaan - Jamu, Maria Endang; Tauk, Andreas Corsini (LPPM Universitas Flores, 2023)
The problem in the Watu Village, Langke Rembong District, Manggarai Regency, East Nusa Tenggara Province community is the limited knowledge of mothers in managing the cassava harvest and the low level of knowledge. The processed cassava is still very limited. The entrepreneurial spirit is still so low, women have not thought about how to turn cassava into a product that has a selling value and can be marketed to consumers. Therefore, the student KKN program is a means to help provide understanding to mothers in Watu Village to foster interest in entrepreneurship. The focus of this activity is on empowerment and socialization related to entrepreneurship. This program aims to foster interest in entrepreneurship for mothers so that they can increase their income. The program’s implementation method is socialization and assistance in processing cassava products. The results and impacts of the KKN students' activities for mothers in Watu Village are firstly an increase in mothers' knowledge about entrepreneurship and secondly an increase in mothers' awareness of processing cassava into several product variants with economic value.